Pengaruh Model Problem Based Learning Berbasis Potensi Lokal pada Pembelajaran Biologi terhadap Kemampuan Literasi Sains Siswa Kelas X SMA Negeri 1 Cepogo - Amytia Putri; Suciati Sudarisman; Murni Ramli (Universitas Sebelas Maret, 2014)
Purpose of this research is to know the influence of of Problem Based Learning based on localities models toward scientific literacy of students of grade X. The research was a quasy experimental research used posttest only non-equvalent control groups. Population of the reserach was the students of grade X in the second semester of SMA N 1 Cepogo in the academic year 2013/2014. Sampling technique was cluster sampling method. Collected data was connucted by test and non test method. The test for measuring scientific literacy was a five essay test, which consist of three aspects, namely: to identify scientific issues, to explain phenomena scientifically, and to use scientific evidence. The non test method were observation, and documentation. Hypothesis test were analysed by t-test using SPSS version 16. The results of the research were received H1 and rejected H0. It means there was a difference of scientific literacy between control class (conventional models) and experiment class using Problem Based Learning based on localities. The average score of scientific literacy in experimental class was 48,47 and score of control class was 26,95. It was also found that the highetst average of scintific literacy in the experimental class was aspect to use scientific evidence, while the lowest one was to identify scientific issues. The conclusion of the research was Problem Based Learning based on localities models significantly influenced the scientific literacy of grade X students SMA N 1 Cepogo. Key Words: Problem Based Learning, scientific literacy, based on localities